THE APPLICATION OF SEMANTIC GRADATION IN UZBEK LANGUAGE EXPLANATORY DICTIONARIES (TAMADDUN NURI JURNALI, 2025)
This article investigates the application of the semantic categorization of lexemes provided in Uzbek explanatory dictionaries. It presents opinions and reflections on the application of the principle of categorization in explanatory dictionaries.